Effects of chromium, and ascorbic acid supplementation on growth, carcass traits, serum metabolites, and antioxidant status of broiler chickens reared at a high ambient temperature (32°C) - Şahin, Kazım; Şahin, Nurhan; Küçük, Ömer (Pergamon-Elsevier Science Ltd, 2003)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate, CrPic) and vitamin C (L-ascorbic acid) supplementation on performance, carcass characteristics, and serum concentrations of T-3 (Triiodothyronine), T-4 (Thyroxine), insulin, corticosterone, glucose, cholesterol, MDA as indicator of lipid peroxidation (Malondialdehyde), vitamin C, and vitamin E in broiler chickens (Ross) reared under heat stress (32degreesC). One day-old 120 male broilers were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The-birds were fed either a basal diet or the basal diet supplemented with either 400 mg of Cr/kg of diet, 250 mg of L-ascorbic acid/kg of diet, or 400 mg of Cr plus 250 mg of L-ascorbic acid/kg of diet. Separately or as a combination, supplemental chromium and vitamin C increased body weight gain (P < 0.01) and feed intake (P < 0.01), and improved feed efficiency (P < 0.05). The supplements also increased hot and chilled carcass weights and yields (P < 0.05) as well as liver, heart, spleen, and gizzard weights (P < 0.05). However, abdominal fat decreased (P < 0.05) upon dietary chromium and vitamin C supplementation. Separately or as a combination, supplemental chromium and vitamin C resulted in an increase in serum insulin, T-3, T-4, but a decrease in corticosterone (P < 0.05), glucose and cholesterol (P < 0.05) concentrations. Supplemental chromium and vitamin C also increased serum concentrations of vitamin C and vitamin E (P < 0.05) but, decreased MDA concentrations (P < 0.01). The results of the study show that, separately or as a combination, vitamin C and chromium supplementation resulted in an improved live weight gain, feed efficiency, and carcass traits, as well as a decrease in serum corticosterone and MDA concentrations. The results of the present study also suggest that vitamin C and chromium have similar effects and that a combination of vitamin C (250 mg/kg of diet) and chromium (400 mg Cr/kg of diet) may offer a potential protective management practice in preventing heat stress-related depression in performance of broiler chickens. (C) 2003 Elsevier Science Inc. All rights reserved.
Keywords: broiler; heat stress; chromium; vitamin C; MDA